ANGPTL4 gene E40K variation protects against obesity‐associated dyslipidemia in participants with obesity. (26th December 2018) - Bailetti, D.; Bertoccini, L.; Mancina, R. M.; Barchetta, I.; Capoccia, D.; Cossu, E.; Pujia, A.; Lenzi, A.; Leonetti, F.; Cavallo, M. G.; Romeo, S.; Baroni, M. G.
Summary: Objective: ANGPTL4 inhibits lipoprotein lipase in adipose tissue, regulating plasma triglycerides levels. In persons with obesity plasma ANGPTL4 levels have been positively correlated with body fat mass, TG levels and low HDL. A loss‐of‐function E40K mutation in ANGPTL4 prevents LPL inhibition, resulting in lower TGs and higher HDLc in the general population. Since obesity determines metabolic alterations and consequently is a major risk factor for cardiovascular disease, the aim was to explore if obesity‐related metabolic abnormalities are modified by the ANGPTL4 ‐E40K mutation. Methods: ANGPTL4 ‐E40K was screened in 1206 Italian participants, of which 863 (71.5%) with obesity. All subjects without diabetes underwent OGTT with calculation of indices of insulin‐sensitivity. Results: Participants with obesity carrying the E40K variant had significantly lower TG ( p = 0.001) and higher HDLc levels ( p = 0.024). Also in the whole population low TGs and high HDLc were confirmed in E40K carriers. In the obese subpopulation it was observed that almost all E40K carriers were within the lowest quartile of TGs ( p = 1.1 × 10 −9 ). E40K had no substantial effect of on glucose metabolism. Finally, none of the obese E40K carriers had T2D, and together with the favourable lipid profile, they resemble a metabolically healthy obese (MHO) phenotype, compared to 38% of E40E wild‐type obese that had diabetes and/or dyslipidaemia ( p = 0.0106). Conclusions: In participants with obesity the ANGPTL4 ‐E40K variant protects against dyslipidemia. The phenotype of obese E40K carriers is that of a patient with obesity without metabolic alterations, similar to the phenotype described as metabolic healthy obesity.